Mapping Channel Distribution Based on Seismic and Well Data in West Natuna - Ikramina, Alma; Haryanto, Iyan; Abdurrokhim, . (Bulletin of Scientific Contribution, 2021)
Natuna is one of the regions in Indonesia that has potential in hydrocarbon with a siliciclastic reservoir which is generally characterized by a fluvial and deltaic environment. For this reason, it is important to identify the distribution channel to find out the distribution of the reservoir. This study using the well-logging and 3D seismic data interpretation methods. With the correlation between the horizon slicing method on seimsic data, lithology identification in well data, and also using seismic attributes, we can determine the distribution of reservoirs. In reseach area, reservoir distribution analysis in Arang and Muda Formation. Where Arang Formation identified 4 reservoirs, which 3 of them have oil content, with effective porosity value of 10-30%. Meanwhile, in Muda Formation, there are 3 reservoirs with effective porosity of Muda Formation is 20-27%